2013
DOI: 10.1016/j.apmr.2013.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stimulating Hip and Trunk Muscles on Seated Stability, Posture, and Reach After Spinal Cord Injury

Abstract: Objective To determine the stimulated strength of the paralyzed gluteal and paraspinal muscles and their effects on the seated function of individuals with paralysis. Design Case series with subjects acting as their own concurrent controls. Setting Hospital-based clinical biomechanics laboratory. Participants Eight users of implanted neuroprostheses for lower extremity function with low-cervical or thoracic level injuries. Interventions Dynamometry and digital motion capture both with and without stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 26 publications
3
56
1
Order By: Relevance
“…It has been established previously that individuals with poor trunk control engage in a posterior pelvic tilt and show an increased thoracic kyphosis in sitting to increase their base of support. 11,12 Sprigle et al 13 demonstrated that with posterior pelvic tilt functional reach distance increased. This compensatory strategy may increase reach ability, due to increased base of support through contact of the sacrum to the supporting surface and posterior displacement of the center of mass over the base of support, offsetting the anterior displacement of the center of mass during forward reaching.…”
Section: Study Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been established previously that individuals with poor trunk control engage in a posterior pelvic tilt and show an increased thoracic kyphosis in sitting to increase their base of support. 11,12 Sprigle et al 13 demonstrated that with posterior pelvic tilt functional reach distance increased. This compensatory strategy may increase reach ability, due to increased base of support through contact of the sacrum to the supporting surface and posterior displacement of the center of mass over the base of support, offsetting the anterior displacement of the center of mass during forward reaching.…”
Section: Study Limitationsmentioning
confidence: 99%
“…10 With increased trunk instability, the individual with SCI may engage in a posterior pelvic tilt and an increase in thoracolumbar kyphosis. These compensatory strategies increase the base of support thereby improving sitting balance 11,12 resulting in increased functional reach. 13 Hand-held dynamometry of the upper and lower extremity muscles has been shown to have high interclass correlation coefficient (ICC = 0.86-0.97) and intra-rater (ICC = 0.89-0.97) reliability in individuals with neuropathic weakness.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary studies on simple on-off control of FNS to the hip and lumbar trunk extensors have shown promise of immense benefits. 9,10 Ideas from the current study will help in designing more advanced interventions that can improve the daily independent functioning of SCI individuals.…”
mentioning
confidence: 99%
“…Stiffening the otherwise paralyzed trunk and hip extensor muscles with continuous electrical stimulation can correct kyphotic seated posture, expand bimanual workspace, improve ventilation, alter interface pressures, statically stabilize the trunk, and improve manual wheelchair propulsion efficiency [1,[15][16][17][18]. However, this strategy substitutes one statically stable posture for another.…”
Section: Introductionmentioning
confidence: 99%
“…Pulse widths were tuned for each stimulation channel to maintain sagittal and coronal alignment of the trunk in a static, erect seated posture. This continuous pattern was generally used by the participants in their home environments [15,[17][18]. For all subjects, stimulus pulse widths and amplitudes were chosen that would avoid interference with respiration or the discomfort sometimes associated with activating the abdominal muscles or sensory fibers near the stimulating electrode.…”
Section: Stimulation Patternsmentioning
confidence: 99%